Characteristics of a Cohort of Home Parenteral Nutrition Patients at the Time of Enrollment in the Sustain Registry. (November 2016) - Winkler, Marion F.; DiMaria-Ghalili, Rose Ann; Guenter, Peggi; Resnick, Helaine E.; Robinson, Lawrence; Lyman, Beth; Ireton-Jones, Carol; Banchik, Lillian Harvey; Steiger, Ezra
Background: Home parenteral nutrition (HPN) is a vital lifesaving therapy for patients who are unable to maintain weight, fluid balance, nutrition, and functional status via oral or enteral nutrition alone. There are few current data sources describing HPN prevalence, patient demographics, or long-term outcomes in the United States. Objective : To describe demographics and baseline characteristics of patients receiving HPN therapy. Methods : This is a descriptive analysis of data from the first cohort of HPN patients at time of enrollment in the Sustain TM Registry between August 2011 and February 2014. Results : There were 1251 patients enrolled from 29 sites. Eighty-five percent of patients were adults, with a mean age of 51.3 ± 15.3 years. Fifteen percent were pediatric, with a mean age of 4.9 ± 4.9 years. For both age groups, short-bowel syndrome was the most frequently reported HPN indication (24%). Adults most commonly had a peripherally inserted central catheter (47%) or a tunneled catheter (43%) for HPN administration. In contrast, most pediatric patients (72%) had a tunneled catheter. Most patients received parenteral nutrition daily and consumed some oral nutrition. Twenty-eight percent of all patients were expected to require HPN indefinitely. Conclusions : This is the first report of descriptive data from the Sustain Registry. The data reveal important characteristics of patients receiving HPN in 29 U.S. sites.